Primary dictionary. - Macmillan/McGraw-Hill School Publishing Company (London : Harper Collins, 1991)
A dictionary for beginning readers and writers, featuring alphabetically arranged entries, with definitions, illustrations, and photographs. Includes a selection of reference materials and resources.
2.1
K-3
Keywords: English language -- Dictionaries, Juvenile; Picture dictionaries; Picture dictionaries